The Effect of Leader Support and Competence to the Organizational Commitments on Employees Performance of Human Resources Development Agency in West Kalimantan - Waldan, Raziki (Fakultas Ekonomi dan Bisnis, UNTAN, 2020)
The performance on employees of Human Resources Development Agency in West Kalimantan can be said to be not optimal when viewed from the accuracy of their internal reporting The results of this study can be concluded: 1) there is an influence of leader support on organizational commitment of employees of the Human Resource Development Agency in West Kalimantan. It can be proven empirically that the higher the suitability between the leader's support and its members, it will increase organizational commitment to employees; 2) there is the influence of leaders' support on the performance of employees of the Human Resources Development Agency in West Kalimantan; 3) there is an influence of competence on organizational commitment of employees of the Human Resource Development in West Kalimantan. This is the higher competence of employees, the higher the commitment of employees of the human resource development in West Kalimantan. There is the influence of competence on the performance of employees of the Human Resource Development Agency in West Kalimantan; 4) there is an organizational influence on the performance of employees of the Human Resources Development Agency in West Kalimantan.